Tax Court Decisions as the Ultimum Remedium for Taxpayers - Gunawan, Edy (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2023)
Taxes obtained can directly finance all state activities. State revenues, while coming from tax revenues, are also obtained from revenues outside of taxes which consist of 3 parts, which can be seen as income, capital or money to finance total government activities as shown in Law Number 17 of 2003 concerning State Finance, which can be explained in principle as follows. First, State revenues are derived from tax revenues. Second, non-tax government revenue. Thirdly, government revenue from grants. The third principle is referred to as state revenue from the tax sector and is still the largest source of revenue for state revenue. Research objectives in this paper are issues concerning taxation provisions; the application of the ultimum remedium is highly dependent on the prevailing priority scale with its main emphasis on optimizing state revenue, and not on the so-called criminal aspect; with the main reason being that the perpetrators of tax crimes should be responsible and continuously return or repair all losses incurred as a result of their mistakes. The method used is normative legal research by elaborating field data with secondary data in the form of primary, secondary and tertiary legal materials to be analyzed qualitatively. The results to be achieved in this study are willing to develop an overall understanding of tax court decisions as an ultium remedium effort for taxpayers. The application of the ultimum remedium principle directly is to increase state revenue, especially revenue in the sector.